The marine environment protection: Topical issues" system of international rules and principles, ways and means of co-operation. (Ground plane) - Łukaszuk, Leonard (Studia Ecologiae et Bioethicae, 2003)
The author discusses the main sources of marine environment pollution and measures to prevent, reduce, and control to ensure effective protection, and cooperation on a global or regional basis. Legal measures have been included for enforcement with respect to the marine environment from harmful effects that may arise from pollution from land-based sources, pollution by dumping, pollution from vessels, and pollution from activities in the Area. Enforcement comprises proper measures by flag and port States as well as coastal States. Topical issues have been discussed rules and principles regulated by the United Nations Convention on the Law of the Sea (1982). i.e. uses of the seas and oceans, the conservation of their living resources" and the study, protection, and preservation of the marine environment. Also, the same selected matters of the marine environment protection and regional co-operation in Europe as well as in Asia and Pacific rims have been included.